PARTISIPASI IBU MENGIKUTI PROGRAM IMUNISASI BALITA PADA POSYANDU DWI KARYA DI DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Jas, Jasfar; ', Hazirah; ', Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated state National Development carried out evenly across the country, planning, and purposeful, all Integrated Service Post, or Posyandu is part of the health development programmed by the government. IHC also be referred to as unit non-formal education where posyandu also a learning group in society, study groups can occur during Posyandu activities take place, Posyandu cadre known as a facilitator and a member posyandu as learners, the facilitator serves as a conduit motivator, extension officer , and health services. The research problems are how high the participation of mothers to follow infant immunization program in posyandu Dwi Karya In the village of Tanjung Hulu subdistrict Koto Kampar Kampar District? The purpose of this study was to determine the level of participation of mothers to follow infant immunization program in posyandu Dwi Karya In the village of Tanjung Hulu subdistrict Koto Kampar Kampar regency. This type of research used in this research is descriptive quantitative approach population in this study as many as 243 people. Then the sample is 70 people and 30 people a test sample, the sample used is simple random sampling. Data collection instrument is a questionnaire with 42 statements and after the trial to 35 valid statement to be made in research instrument. Data analysis through quantitative descriptive analysis. The results of research and discussion in accordance with the objectives of this research from the calculation presentation of the answers obtained by the research findings participation of mothers in following immunization of infants in posyandu Dwi Karya In the village of Tanjung District of Koto Kampar Hulu Kampar, it can be concluded the average percentage (SL + SR ) 41.502%. This means that mothers of children aged under five in the village of Tanjung Hulu subdistrict Koto Kampar Kampar regency have relatively low response to activities at Posyandu Dwi Karya in Tanjung.Keywords: Participation, Participation Of Mothers, Following Infant Immunization Program